Impact of Modernity and Tradition on Indian As Well As Western Literature With Respect to Colonial Influence: Exploring the Interplay of Tradition, Modernity, and Colonialism in Indian and Western Literature (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper investigates how the language of tradition and modernity has been the dominant idiom that has looked to catch the essence of both the Indian country and the Indian lady. The striking nature of this talk requests a critical enquiry to see how this larger and authoritative idiom been acknowledged as an unproblematic given. India is frequently observed as a place that is known for complexities where tradition and modernity exist together where Indian ladies are regularly displayed as symbolic of this conjunction. India, with its colonial history and contemporary postcolonial culture, offers a rich site for the investigation of both impact and intersexuality. Through the ascent of Orientalism, it was India which originally practiced a literary impact on the West, an equation that was completely reversed later through colonial intervention.